SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN PADA KELURAHAN SAMPANGAN SEMARANG (Fakultas Teknologi Informasi Universitas Stikubank (Unisbank) Semarang, 2013)
The rapid development of computer technology along with the development of software and hardware, in a lot of computer development plays an important role in life to support human performance in completing tasks - tasks. This thesis is taking the issue of how to design and create a program of population information system applications using Visual Basic 6.0, as research conducted in the Village Sampangan Semarang. Population information system application program was created using Visual Basic 6.0. That is a software built by Microsoft as Visual Studio and Visual Basic is part of Visual Studio that can be used to design a few pieces to form master will result in report creation step programs: A study of the object, system analysis, system design, and testing. In the Population Information System application program there is some discussion that includes: Main Menu Form, Form Master data population, transactions Form Data Entry, Data Move Transactions Form, Form Data Transaction Births, Deaths and Form Data Transaction Reports. Keywords: VB.6.0, Population, Population Information System